Comparison of serum levels of hepcidin and pro-hepcidin in hemodialysis patients and healthy subjects - N Taheri; Gh Roshandel; M Mojerloo; M Hadad; H Mirkarimi; R Khorasani Nejad; H R Joshaghani (Saudi Journal of Kidney Diseases and Transplantation, 2015)
Hepcidin prevents absorption of iron from the intestine and inhibits release of iron from macrophages and hepatocytes. For this reason, it seems that high levels of hepcidin are a predisposing factor for anemia in chronic inflammatory conditions such as chronic kidney disease and dialysis patients. This study was designed to determine the role of changes in the level of serum hepcidin in the management of hemodialysis patients. This study included 44 dialysis patients and 44 controls. The hepcidin and pro-hepcidin levels were measured by the enzymelinked immunosorbent assay method. The serum ferritin level was measured by the chemiluminescence method. The mean hepcidin level was 999.3 ± 996.7 ng/mL in the case group and 770.4 ± 815.9 ng/mL in the control group (P = 0.25). The mean pro-hepcidin level was, respectively, 186.1 ± 220.3 pg/mL and 150.87 ± 207.7 pg/mL, in the case group and control groups (P = 0.45). The mean (standard deviation) ferritin level was 816.4 ± 379.4 ng/mL in the case group and 193 ± 171.8 ng/mL in the control group (P < 0.001). In the case group, the correlation between serum ferritin and hepcidin was not significant (r = 0.6, P = 0.08). Also, there was no significant correlation between serum ferritin and pro-hepcidin levels (r = 0.6, P = 0.08). A positive correlation was seen between pro-hepcidin and hepcidin levels (r = 0.92, P < 0.01). In this study, the results showed that the serum hepcidin levels are high in dialysis patients and that there was no correlation with the serum ferritin levels.